2022
DOI: 10.1101/2022.07.03.498529
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Signal peptide mimicry primes Sec61 for client-selective inhibition

Abstract: Preventing the biogenesis of disease-relevant proteins is an attractive therapeutic strategy, but attempts to target essential protein biogenesis factors have been hampered by excessive toxicity. Here, we describe KZR-8445, a cyclic depsipeptide that targets the Sec61 translocon and selectively disrupts secretory and membrane protein biogenesis in a signal peptide-dependent manner. KZR-8445 potently inhibits the secretion of proinflammatory cytokines in primary immune cells and is highly efficacious in a mouse… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…In the cryo-EM structure, the macrocyclic cotransin inhibitor is bound to the Sec61 complex with an open lateral gate and a closed plug helix (Rehan et al 2022). This is similar as observed in the cryo-ET study of the Sec61/TRAP complex in the ER membrane, where surprisingly the lateral gate was observed to be open in majority of Sec61 molecules (Pfeffer et al 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the cryo-EM structure, the macrocyclic cotransin inhibitor is bound to the Sec61 complex with an open lateral gate and a closed plug helix (Rehan et al 2022). This is similar as observed in the cryo-ET study of the Sec61/TRAP complex in the ER membrane, where surprisingly the lateral gate was observed to be open in majority of Sec61 molecules (Pfeffer et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…3H ). The simulations were initiated starting from an open conformation observed in our structure of Sec61 primed with a macrocyclic cotransin inhibitor (Rehan et al 2022). In simulations without TRAP, we observed the lateral gate closing rapidly, whereas simulations with TRAP included retained an open lateral gate conformation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data suggest that the density feature previously assigned as mycolactone is unlikely to be mycolactone. During the preparation of this manuscript, a medium-resolution cryo-EM structure of the mammalian Sec61 channel in association with a ribosome and a cotransin derivative has been reported 53 . While the overall structure of the channel and the location of the binding pocket seem consistent with ours, we note that the orientation of the inhibitor model is substantially different from that of cotransin from our study.…”
Section: Resultsmentioning
confidence: 99%
“…A recent cryo-EM study of the Sec61 translocon exposed to a novel cotransin analog, KZR-8445 containing a large cyclic heptadepsipeptide ring, reveals binding of the inhibitor to the SPbinding cleft (53). Another recent Sec61 structural study of multiple translocation inhibitors, including mycolactone and CADA, showed an overlapping binding site near the lateral gate of Sec61 for all the inhibitors (50).…”
Section: Different Inhibitor Binding Sites In Sec61mentioning
confidence: 99%